1994
DOI: 10.1111/j.1365-4362.1994.tb02862.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PERFECT STATE OE TRICHOPHYTON VIOLACEUM

Abstract: This is the first report on the production of the perfect (sexual) state of T. violaceum. Details of the ascogenous form of this dermatophyte should be studied in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…M. canis was responsible for most cases in this study followed by M. audouinii (52% and 36% respectively). Earlier studies in Egypt reported that T. violaceum was the most common isolated organism and in some studies was the only isolated dermatophyte causing tinea capitis ( Table 4 ) 12 13 17 19 20 21 . It seems that there is an epidemiological change regarding the etiological agent in our region.…”
Section: Discussionmentioning
confidence: 97%
“…M. canis was responsible for most cases in this study followed by M. audouinii (52% and 36% respectively). Earlier studies in Egypt reported that T. violaceum was the most common isolated organism and in some studies was the only isolated dermatophyte causing tinea capitis ( Table 4 ) 12 13 17 19 20 21 . It seems that there is an epidemiological change regarding the etiological agent in our region.…”
Section: Discussionmentioning
confidence: 97%
“…In Kenya it is the second agent after Microsporum audouinii [6]. Trichophyton violaceum is one of the main agents of epidermomycosis in Egypt [7] and South Africa [8]. In many of these countries, schoolchildren and mothers are healthy carriers.…”
Section: Discussionmentioning
confidence: 99%
“…T. violaceum has been reported as the most common pathogen in north Africa (Egypt and Libya), east Africa (Ethiopia), the Middle East (Iraq and Jordan) and the Far East (Pakistan and India) 2–10 . The fungus also persists in many other countries of Middle East and Africa, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Trichophyton violaceum infections are endemic in eastern Europe, in some regions of Africa mainly in the north, in the Middle East and the Far East 1–10 . On the contrary, the incidence rate of T. violaceum infections in north‐western Europe and North America is very low and isolates are restricted mainly to immigrants from countries where the infection is endemic 11–13 …”
Section: Introductionmentioning
confidence: 99%